Contractual-based Islamic crowdfunding model for sustainable agricultural financing - Fahlevi, Rizal; Hosen, Muhammad Nadratuzzaman; Amalia, Euis (Jurnal Ekonomi & Keuangan Islam, 2026)
Purpose – This study develops a Sharia-compliant crowdfunding model based on digital technology that integrates four principal contracts in Islamic jurisprudence (salam, istisna’, muzara’ah, and musaqah) to enhance the relevance and effectiveness of agricultural financing in Indonesia.Methodology – Using a qualitative exploratory approach, we combine relevant literature and content analyses of agricultural crowdfunding campaigns. The model’s internal validity is reinforced through triangulation involving Islamic legal theory, and nationally recognized Sharia regulatory guidelines issued by the Indonesian National Sharia Council (DSN-MUI). Empirical campaign data. were obtained from 15 agricultural crowdfunding campaigns published during 2021-2024 period and validated through thematic analysis and triangulation across documents and campaign reports.Findings – The findings reveal that most existing campaigns rely on single contracts, such as salam or murabahah, which are inadequate for the seasonal and high-risk nature of agriculture. The proposed multi-contract model offers a more equitable and Sharia-aligned financing framework that accommodates joint risk sharing and production-based returns. Furthermore, digital integration allows for the development of more inclusive, adaptive, and dynamic contracts.Implications – Theoretically, this study contributes to the Islamic finance literature by introducing a risk-sharing, partnership-oriented financing framework tailored to the agricultural sector. Practically, the model provides actionable insights for Sharia-compliant crowdfunding platforms and financial regulators to promote inclusive and sustainable agricultural finance.Originality – This study contributes to the literature by proposing a conceptual model of multi-contract agricultural crowdfunding, a novel approach that bridges normative Sharia principles with empirical evidence in the context of Islamic digital financial innovation.